Xanthium spinosum L. Extracts Inhibit Breast Cancer in Mice by Apoptosis Induction and Immune System Modulation - Lina T. Al Kury; Zainab Taha; Asma Ismail Mahmod; Wamidh H. Talib (Pharmaceuticals, 2022)
Plants have been considered for many years as an important source of medicine to treat different diseases. Xanthium spinosum L. (Asteraceae, Compositae) is known for its diuretic, anti-inflammatory, and sedative effects. It is also used in the treatment of several ailments, such as cancer. In order to evaluate the anticancer and immunomodulatory activities, crude ethanol extract was prepared from the aerial part of X. spinosum and then fractionated using solvents with different polarities. As well, the chemical composition of X. spinosum extract and fractions were identified using LC-MS analysis. The antitumor effect of X. spinosum was assessed in both in vitro and in vivo models. Apoptosis induction was measured in vitro using a caspase-3 activity kit. Lymphocyte proliferation and phagocytosis and pinocytosis induction were used to quantify the effect of the plant extract and fractions on acquired and innate immunity, respectively. The effect of X. spinosum extract, and fractions on the levels of cytokines (IFN-γ, IL-2, IL-4, and IL-10) in murine lymphocytes was determined using a mouse-uncoated TH1/TH2 ELISA kit. Results showed that ethanol extract had the highest antiproliferative activity (IC₅₀ = 2.5 mg mL−1) against EMT6/P cell lines, while the aqueous and chloroform fractions had the highest apoptotic activity with 2.2 and 1.7 folds, respectively. On the other hand, the n-hexane fraction was the most effective in stimulating lymphocyte proliferation, whereas ethanol extract, aq. Methanol and aqueous fractions exhibited the highest phagocytic activity. As well, X. spinosum extract and fractions were able to modulate the expression of IL-2, IL-4, and IFN-γ. A remarkable decrease in tumor size was accomplished following the treatment of tumor-bearing mice with X. spinosum extract and fractions. Both aq. Methanol and chloroform fractions showed the highest percentage change in tumor size with -58 and -55%, respectively. As well, tumor-bearing mice treated with chloroform fraction demonstrated a high curable percentage with a value of 57.1%. Anyway, X. spinosum extract and fractions exhibited no toxic impact on the liver or kidney functions of the mice-treated groups. These findings may confirm that X. spinosum has favorable anticancer and immunomodulatory effects. However, additional studies are required to fully understand the mechanisms of action of this plant and the signaling pathways involved in its effects. Moreover, more testing is needed to have better insight into the apoptotic pathway and to know the exact concentration of active compounds.